Enhancing vertical-axis wind turbine self-starting with distinctive blade airfoil designs - Muhammad Shaaban Abul-Ela; Mohamed ElFaisal ElRefaie; Ashraf Ibrahim Sayed (Journal of Engineering and Applied Science)
Abstract The starting issue of the Darrieus vertical-axis wind turbine is a crucial challenge, particularly at low tip-speed ratios. This paper demonstrates a solution to overcome the self-starting issue for this turbine type by studying the influence of various blade airfoils in light of their kind and orientation. The proposed airfoils included symmetric airfoils NACA0012 (reference model), E474, and S1048 in addition to cambered airfoils S1210, NACA6712, DU-06-W-200, Clark Y, and FX 63–137. Numerical simulations based on a finite-volume method software, ANSYS Fluent, were executed utilizing the SST-k-ω as a turbulence model to solve unsteady Reynolds-averaged Navier–Stokes equations. The numerical model was validated against available published experimental data. The results indicated that the cambered-in-oriented NACA6712 airfoil was the most effective at low tip-speed ratios (TSRs) ranging from 1.2 to 2.4. At a TSR of 2.0, its power coefficient (C p) increased by approximately 180% compared to the reference airfoil at the same TSR. Furthermore, the E474 airfoil performed efficiently at mid-to-high TSRs (2.0 to 3.3). Its peak power coefficient is enhanced by about 19.5% at TSR = 3.0 relative to the reference model at the same TSR. On the other hand, the S1210, Clark Y, and FX63-137 cambered-in-oriented airfoils performed poorly at all TSR ranges (1.2 to 3.5). Nevertheless, the flipping of the camber of these airfoils outward provided a significant improvement in the power coefficient and the torque coefficient relative to the cambered-in-oriented ones. The Clark Y in the flipped orientation performs best at all TSR ranges relative to other flipped airfoils. As a result, NACA6712 was the optimum blade profile chosen for low TSRs, whereas E474 was suitable for mid-to-high TSR zones.